Does the shadow economy have a significant impact on tax revenues in ASEAN? - Song, Kosal (Edelweiss Applied Science and Technology, 2025)
The analysis incorporated four variables: the shadow economy, Gross Domestic Product (GDP), Foreign Direct Investment (FDI), and foreign exchange, which were examined through three static panel data models—Pooled Ordinary Least Squares (OLS), Random Effects (RE), and Fixed Effects (FE). The empirical results indicated that an increase in the shadow economy is positively associated with higher tax revenues in ASEAN member states, with the estimated coefficient being both positive and statistically significant at the 1% level. Similarly, GDP and foreign exchange showed a positive relationship with tax revenues, also significant at the 1% level. Additionally, FDI exhibited a positive and statistically significant relationship with tax revenues at the 5% level, suggesting that higher FDI flows are linked to increased tax revenues in the ASEAN region. The results remained consistent across all panel data models, with the RE model identified as the most appropriate, as confirmed by the Hausman test.